2002
DOI: 10.1099/0022-1317-51-12-1041
|View full text |Cite
|
Sign up to set email alerts
|

Isolation from a sheep of an attaching and effacing Escherichia coli O115:H− with a novel combination of virulence factors

Abstract: Attaching and effacing (AE) lesions were observed in the caecum, proximal colon and rectum of one of four lambs experimentally inoculated at 6 weeks of age with Escherichia coli O157:H7. However, the attached bacteria did not immunostain with O157-specific antiserum. Subsequent bacteriological analysis of samples from this animal yielded two E. coli O115:H 2 strains, one from the colon (CO) and one from the rectum (RC), and those bacteria forming the AE lesions were shown to be of the O115 serogroup by immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Cookson et al [9] experimentally inoculated four lambs at 6 weeks of age with an E. coli O157:H7. Attaching-effacing lesions were observed in the caecum, proximal colon and rectum of one lamb.…”
Section: East1 In Sheepmentioning
confidence: 99%
“…Cookson et al [9] experimentally inoculated four lambs at 6 weeks of age with an E. coli O157:H7. Attaching-effacing lesions were observed in the caecum, proximal colon and rectum of one lamb.…”
Section: East1 In Sheepmentioning
confidence: 99%
“…Primers intF and (zeta) intR, based on GenBank sequence AJ298279 from STEC O84 537/89 (11), were used to detect the eae subtype. The STEC enterohemolysin (ehxA), serine protease (espP), katalase peroxidase (katP), and type II secretion system (etpD) genes were detected using primers outlined previously (5,6,12). PCR analysis indicated that all 22 of the isolates were stx 1 , eae ( subtype), ehxA, and espP positive (Table 1).…”
mentioning
confidence: 99%
“…stx and/or eae detection was performed using a multiplex PCR method outlined previously (6). Primers intF and (zeta) intR, based on GenBank sequence AJ298279 from STEC O84 537/89 (11), were used to detect the eae subtype.…”
mentioning
confidence: 99%
“…It is uncertain whether ruminants are a reservoir of aEPEC which may cause human diarrheal disease or whether human aEPEC strains are distinct from ruminant aEPEC strains. Previous studies have indicated that plasmid-associated virulence factors more commonly associated with STEC, such as EHEC hemolysin (ehxA) (27), serine protease (espP) (6, 13), a catalase/peroxidise system (katP) (5), and a type II secretion pathway (etpD) (28), are occasionally associated with human aEPEC strains (1,3,16,17) and that these same virulence factors may also be associated with ruminant aEPEC (8,(10)(11)(12). In addition, subtyping of ehxA and espP PCR products has indicated that subtypes of these virulence factors are shared between ruminant aEPEC and STEC (10,12).…”
mentioning
confidence: 99%
“…PCR-RFLP analysis of eae, ehxA, and espP amplicons was performed as described previously (10)(11)(12), and amplification of stx 1 , stx 2 , etpD, and katP (catalase/peroxidase) was performed using primers and amplification as outlined in other studies (5,8,9). Only bac-terial strains that were eae positive were included in this study.…”
mentioning
confidence: 99%